Closeness and belongingness: boosting student engagement in Jakarta universities - Genita, Vona Yolanda; Shaabiriina, Gesilva Putri Samya; Marbun, Hetty Mery; Ria, Ondo (Jurnal Studi Komunikasi, 2024)
Aside from academic activities, university life is enriched by extracurricular or community events that foster organisational skills and competency development. According to previous studies, university students who are motivated to grow personally are those who have aspirations for their future careers. Another factor that encourages active participation in organisational activities is a sense of belonging. Students’ active participation will contribute positively to organisational development. This study uses the lens of weak ties theory, which contrasts with the notion that people with strong relationships are more inclined to provide benefits in certain contexts. This study will use network analytic techniques to determine the extent of relationships between university students through UCINET software. The study aims to identify whether weak interpersonal interactions among students can promote their community engagement. The relationship analysis will relate to the level of their sense of belonging, obtained from questionnaire responses. The data were processed using descriptive statistics and multiple linear regression analysis through SPSS. The results demonstrate that weak relationships and a sense of belonging positively impact member engagement in organisation. This study aims to contribute by offering a hitherto limited analysis of student organisations using the weak ties theory and network analysis method.